2014
DOI: 10.46743/2160-3715/2014.1274
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment and Sense of Adequacy in Infertile Couples: A Fundamental Need in Treatment Process of Infertility - A Qualitative Study

Abstract: Many Iranian couples are suffering from infertility, and their needs have remained unexplored thus far; therefore, the purpose of this study was to explore the infertile couples’ needs and experiences during diagnosis and different stages of infertility treatment. Specific research question included: What are infertile couples’ viewpoints and perceptions about their needs in treatment process of infertility? Researchers used a qualitative design, based on a content analysis approach to analyze in-depth unstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Prior research has shown only half of infertile couples in the US are able to afford treatment (Inhorn & Patrizio, 2015;Kessler et al, 2013), with little progress for the uninsured or underinsured (Berger et al, 2013). Financial burden may be a main factor that contributes to treatment delay or dropout (Mosalanejad et al, 2013;Zargham-Boroujeni et al, 2014). One of our participants poignantly said, "It's not a 'want.'…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Prior research has shown only half of infertile couples in the US are able to afford treatment (Inhorn & Patrizio, 2015;Kessler et al, 2013), with little progress for the uninsured or underinsured (Berger et al, 2013). Financial burden may be a main factor that contributes to treatment delay or dropout (Mosalanejad et al, 2013;Zargham-Boroujeni et al, 2014). One of our participants poignantly said, "It's not a 'want.'…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the challenges of treatment, infertility represents a life crisis for many women and requires psychological, emotional, and spiritual care (Zargham-Boroujeni et al, 2014). Infertility can contribute to various negative psychological sequelae including isolation, frustration, depression, anxiety, hopelessness, guilt, and feelings of worthlessness, failure and inadequacy (Hasanpoor-Azghdy et al, 2014;Hocaoglu, 2018).…”
Section: Introductionmentioning
confidence: 99%